REPRESENTAÇÕES DE ESTUDANTES INGRESSANTES NA ESEF/UFRGS SOBRE A FORMAÇÃO INICIAL EM EDUCAÇÃO FÍSICA - Natacha da Silva Tavares; Elisandro Schultz Wittizorecki; Vicente Molina Neto (Universidade Estadual do Oeste do Paraná, 2014)
This study aimed to identify the representations of students entering the ESEF/UFRGS on the graduation in Physical Education (PE), and understand the construction of these representations. The research was conducted at the School of Physical Education at UFRGS in the first semesters of implementing a new curriculum for the course of PE. This is a qualitative study. Data collection was done through semi-structured interviews with seven students- selected from the typological representativeness criteria using the following criteria: be from different school systems (public and private); some enrolled in the morning shift and the other in the afternoon; some male and the other female; different chronological ages and different expectations of professional performance - the course of PE (ESEF/UFRGS), entrants in the first half of 2012. The analysis was done by identifying units of meaning and the construction of categories of analysis. The study allowed understand that students have different representations of the graduation in PE, likely related to their previous experience to enroll in the course and its prospects for action. There are some indications that keeps its representations attached to these aspects while others start to the disciplines of the first half was allowed to rebuild some representations.